Mechanical and deformation behaviors of sandy mudstone under triaxial unloading creep testing - Liu, Xue; Ying, Zongquan; Zheng, Fangkun; Duan, Chengshi; Wang, Haiyang; Hao, Yang (Frontiers in Earth Science, 2025)
The deformation caused by excavation unloading has a temporal effect, and its transient mechanical and rheological responses will change to some extent. Currently, most research findings on rheological behaviors are based on loading mechanics. However, the rheological behaviors under the unloading stress path are not considered, so the current findings are often inconsistent with the results of actual mechanical processes. In this study, we conducted preliminary unloading rheological tests of argillaceous sandstone in the Tingzikou Irrigation District under constant axial pressure and gradual unloading confining stress paths to evaluate the triaxial unloading rheological characteristics of the rocks. The test results show that the instantaneous and creep deformations of sandy mudstone increase with the deviational stress under step-by-step unloading of the stress levels; further, under gradual unloading of the confining pressure and greater unloading history, the creep rate as well as creep deformation are larger and the unloading effect and rheological characteristics are more obvious. Based on the experimental results, the unloading rheological behavior of sandy mudstone under this stress path is described well by the Hooke–Kelvin three-element model, and the parameters of the unloading rheological constitutive equation for sandy mudstone can be obtained through regression fitting.